Cross-cultural adaptation and validation of the European Portuguese version of the heartland forgiveness scale - Ikedo, Fabio (2020)
Background Forgiveness is linked with well-being, and social and health research has focused on the role and aspects of forgiveness that has been recently suggested as a phenomenon of public health importance. The Heartland Forgiveness Scale (HFS) was developed gathering three subscales to assess the forgiveness of others, forgiveness of self, and forgiveness of situation. The present study aimed to adapt the HFS into European Portuguese, and investigate its reliability and validity. Methods Translation and cross-cultural adaptation were conducted using a multistep forward-back translation process. Internal consistency was assessed by Cronbach’s alpha. Confirmatory factor analysis was conducted to verify that the factor structure is the same as in the original HFS. The short version of the Ruminative Response Scale (RRS) and the Satisfaction with Life Scale (SWLS) were used to examine convergent validity. Results A sample of 222 university students, selected through convenience sampling, was used to access the validity of the European Portuguese version of the HFS (EPHFS). Cronbach’s alpha for the European Portuguese HFS subscales were 0.777, 0.814 and 0.816 for Self, Others and Situation, respectively, indicating acceptable reliability. The 3-factor model of the original HFS was replicated in confirmatory factor analysis. As expected by evidence in the literature, positive and statistically significant correlations were found between SWLS and HFS and subscales. RRS showed negative and statistically significant correlations with HFS and subscales. Conclusions The European Portuguese version of the HFS presented acceptable internal consistency, construct validity and confirmed the three-factor structure of the original HFS.